1979
DOI: 10.1088/0031-9155/24/3/010
|View full text |Cite
|
Sign up to set email alerts
|

Effect on the anatomical structure of the arterial tree on the measurement of pulse wave velocity in man

Abstract: The introduction of an individual anatomical parameter R, taking into account the different lengths of the aorta and of the iliaca-femoralis-tibialis, reduces the individual variability in the measurement of the pulse wave velocity. The dependence of pulse wave velocity on age and pressure is discussed in terms of results obtained by a multivariate analysis of experimental data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1987
1987
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Increased AS has been recently recognized as an independent predictor of future cardiovascular risk [12]. Several reports have also revealed that there are good correlations between aortic root indices and pulse-wave analysis methods [34], and good correlations between aortic stiffness indices which were calculated from aortic root and indices derived from aortography and pulse-wave analysis methods [11]. This study demonstrated that there is a positive correlation between AD and LAEI and SAEI derived from the radial artery pulse-wave analysis method.…”
Section: Discussionmentioning
confidence: 99%
“…Increased AS has been recently recognized as an independent predictor of future cardiovascular risk [12]. Several reports have also revealed that there are good correlations between aortic root indices and pulse-wave analysis methods [34], and good correlations between aortic stiffness indices which were calculated from aortic root and indices derived from aortography and pulse-wave analysis methods [11]. This study demonstrated that there is a positive correlation between AD and LAEI and SAEI derived from the radial artery pulse-wave analysis method.…”
Section: Discussionmentioning
confidence: 99%
“…Manual measurement and feature extraction techniques were often used in the very early days of pulse wave analysis, using various media including chart recorder paper and ruler or photographic recording/magnetic tape (e.g. Hertzman and Spealman (1937), Dillon and Hertzman (1941), Simonson (1956), Corte (1979), Cooke et al (1985), Sherebrin and Sherebrin (1990)). Recent developments in computing technology and software data analysis tools have enabled the sophisticated pre-and post-processing of physiological waveforms.…”
Section: Photoplethysmography Pulse Wave Characterization and Analysismentioning
confidence: 99%
“…However, assessment of the baPWV requires specialized equipment and is time consuming, affecting its practicality in everyday clinical routine. Moreover, the reliability of this technique has been called into question due to its unsatisfactory level of accuracy with regard to brachial‐ankle distance measurements, which are susceptible to the influence of body surface fat, breast size, and abnormalities of the chest or spine 27 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the reliability of this technique has been called into question due to its unsatisfactory level of accuracy with regard to brachial-ankle distance measurements, which are susceptible to the influence of body surface fat, breast size, and abnormalities of the chest or spine. 27 In recent years, studies have found that two-dimensional speckle tracking imaging technology originally used to evaluate myocardial function can also be used as a reliable method for the evaluation of arterial stiffness. 28,29 However, due to the fact that the middle muscular layer of the three-layer structure of the arterial wall is thinner than the myocardial layer, large errors may occur due to the loss of tracking during the analysis.…”
Section: Correlation Analysis Of Ascending Aortic Elastic Variablesmentioning
confidence: 99%